2020
DOI: 10.1007/s00296-020-04539-y
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of shear wave elastography for the evaluation of skin strain in systemic sclerosis

Abstract: The assessment of skin fibrosis is vital for the diagnosis and monitoring of treatment in the systemic sclerosis (SSc)-a severe autoimmune disease. The elastography is a technique of skin fibrosis assessment through the evaluation of skin strain. We compared the efficacy of the shear wave elastography (SWE) and commonly used modified Rodnan skin score (RSS) in skin fibrosis assessment in SSc. The study included 40 SSc patients and 28 healthy individuals, with the exclusion of individuals with other skin/autoim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
2
16
0
2
Order By: Relevance
“…Studies suggest that skin thickness (ST) measured with a US-based modality can replace mRSS examination [1,[9][10][11][12]. This is mainly because of the positive correlation between skin stiffness and the mRSS in these studies [1,11,[13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies suggest that skin thickness (ST) measured with a US-based modality can replace mRSS examination [1,[9][10][11][12]. This is mainly because of the positive correlation between skin stiffness and the mRSS in these studies [1,11,[13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Skin involvement assessed with the mRSS correlates with skin stiffness and thickness. According to personal experience and analyzed studies the authors suggest the use of ultrasound-based techniques, in particular high-frequency ultrasound and shear-wave elastography [9,10,13,14,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, numerous studies have reported on skin stiffness based on manual compression 38,39,54,55 and shear-wave elastography. 44,[56][57][58][59][60][61] Most of these studies reported a significantly higher shear-wave velocity value in SSc patients than in controls, at almost all the Rodnan skin sites (Table 3). Interestingly, four of these studies observed a significantly higher skin stiffness in clinically uninvolved skin, ie, with an mRSS score of 0, in SSc than in healthy controls.…”
Section: Recent Acquisitions In the Use Of Elastography Ultrasound In The Study Of Skin In Systemic Sclerosismentioning
confidence: 99%